2017
DOI: 10.1016/j.jinsphys.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Male sexual enhancement after methoprene treatment in Anastrepha fraterculus (Diptera: Tephritidae): A sustained response that does not fade away after sexual maturation

Abstract: The juvenile hormone (JH) of insects triggers physiological changes related to reproduction in adults of both sexes. Methoprene is a sesquiterpene with some effects that are analogous to those of JH. Treatments with methoprene accelerate sexual maturation in males of the South American fruit fly Anastrepha fraterculus, giving young males a mating advantage over non-treated males of the same age. Here, we evaluated the effects of methoprene treatment on A. fraterculus males after the sexual maturation phase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…[42] and Bachmann et al . [43,44] observed that A. fraterculus females prefer males that had been exposed to volatiles of guava fruit (one of its main hosts) or treated with methoprene (an artificial analogue of JH). Here, we verified these patterns of sexual selection and investigated whether female preferences can be explained on the basis of a direct fitness benefit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[42] and Bachmann et al . [43,44] observed that A. fraterculus females prefer males that had been exposed to volatiles of guava fruit (one of its main hosts) or treated with methoprene (an artificial analogue of JH). Here, we verified these patterns of sexual selection and investigated whether female preferences can be explained on the basis of a direct fitness benefit.…”
Section: Discussionmentioning
confidence: 99%
“…relating their preference with direct fitness benefits) is misleading. In this scenario, methoprene would induce a higher rate of pheromone release in males, which triggers female acceptance over non-treated males [44] by exploiting females’ sensory channel with no reward in terms of their own potential fecundity. However, juvenile hormone analogues do exist in nature [45–47] and some insects consume them, increasing their reproductive output [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila melanogaster Meigen also shows JH-dependent male mating behaviour (Wijesekera et al, 2016). On the other hand, in the South American fruit fl y, Anastrepha frateculus (Wiedemann), treatment with methoprene accelerate sexual maturation of males, but not the enhancement of mating in males close to sexual maturation, suggesting methoprene might act as a pheromone (Bachmann et al, 2017). In the Asian comma butterfl y, Polygonia aureum L., transplantation of active corpora allata into adult butterfl ies in diapause does not induce males to copulate (Endo, 1973), although methoprene or active corpora allata promotes reproductive development in both sexes (Hiroyoshi et al, 2017).…”
Section: Experimental Protocolmentioning
confidence: 99%